Pelatihan Peningkatan Kualitas Pendidik Dalam Mewujudkan Guru Inspiratif Dan Adaptif Terhadap Perubahan Pendidikan Di Era Digital - Ramdanil Mubarok; Jumrianah Jumrianah; Ina Damayanti; Abdul Kadir (Jurnal Pengabdian Masyarakat (Bisma), 2026)
The changing landscape of education in the digital era demands that teachers not only be pedagogically competent, but also adaptable to technology and inspiring in values. This Community Service (PkM) activity aims to improve the quality of education at the Al-Munawwir Islamic Boarding School in South Sangatta through integrated digital literacy training that encompasses professional, spiritual, and ethical aspects. The implementation method uses a participatory training approach with hands-on practice involving 25 teachers and educational staff. The training was carried out in three main stages: delivering conceptual material, practicing using digital tools (Canva for Education, Google Workspace, and Padlet), and professional reflection. The results of the activity showed significant improvements in digital literacy aspects (48%), understanding of the role of inspirational teachers (35%), and awareness of digital ethics (29%). Participants were able to integrate technology into learning in line with the Islamic boarding school's character values and spirituality. In addition to individual improvement, the Al-Munawwir Digital Inspirational Teacher Community (GIDA) was also formed as a forum for sustainability and collaboration after the training. These results reinforce Prensky's digital wisdom theory and support Fullan & Quinn's deep learning framework, which emphasizes the balance between knowledge, skills, and character in education. This activity contributes to the development of an integrative-holistic training model for Islamic boarding school teachers that combines digital skills and value modeling. These findings are expected to be replicated in other faith-based educational institutions to strengthen the professionalism of inspiring, adaptive teachers in responding to educational changes in the digital era.